2015
DOI: 10.1371/journal.pone.0121500
|View full text |Cite
|
Sign up to set email alerts
|

Tonsillectomy versus Tonsillotomy for Sleep-Disordered Breathing in Children: A Meta Analysis

Abstract: ObjectivesTonsillotomy has gained popular acceptance as an alternative to the traditional tonsillectomy in the management of sleep-disordered breathing in children. Many studies have evaluated the outcomes of the two techniques, but uncertainty remains with regard to the efficacy and complications of tonsillotomy versus a traditional tonsillectomy. This study was designed to investigate the efficacy and complications of tonsillotomy versus tonsillectomy, in terms of the short- and long-term results.MethodsWe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 25 publications
0
42
0
1
Order By: Relevance
“…We should also point out that more recent trends have revealed a progressive shift towards tonsillotomy by ENT surgeons with a corresponding decline in tonsillectomies, as there is some evidence indicating reduced post-surgical complication rates in tonsillotomy, such as bleeding, pain scores and related interventions, and briefer recovery period. A meta-analysis that evaluated tonsillectomy and tonsillotomy for OSA in children examined the findings of 10 studies, and showed that there appeared to be no significant differences in the rates of OSA symptomatic relief, quality of life, or in the changes in immune function after surgery [47]. However, tonsillotomy exhibited a much higher risk (more than 3-fold) of OSA recurrence compared to tonsillectomy.…”
Section: Adenotonsillectomy (Tanda)mentioning
confidence: 99%
“…We should also point out that more recent trends have revealed a progressive shift towards tonsillotomy by ENT surgeons with a corresponding decline in tonsillectomies, as there is some evidence indicating reduced post-surgical complication rates in tonsillotomy, such as bleeding, pain scores and related interventions, and briefer recovery period. A meta-analysis that evaluated tonsillectomy and tonsillotomy for OSA in children examined the findings of 10 studies, and showed that there appeared to be no significant differences in the rates of OSA symptomatic relief, quality of life, or in the changes in immune function after surgery [47]. However, tonsillotomy exhibited a much higher risk (more than 3-fold) of OSA recurrence compared to tonsillectomy.…”
Section: Adenotonsillectomy (Tanda)mentioning
confidence: 99%
“…10 Studies, mainly in the pediatric population, have shown a comparable positive effect on improving symptoms with ICDT while reducing postoperative morbidity and complications compared to ECDT. 12,13 Finding and preserving the fibrous capsule while removing all lymphoid tissue can be time consuming especially while training in the technique and operative efficiency must be considered. 14 Residual tonsillar tissue left adherent to the capsule theoretically may regrow leading to recurrent obstructive symptoms or infections.…”
Section: Introductionmentioning
confidence: 99%
“…This meta-analysis [107] was limited to the English literature and compared the outcome of TE vs. TOTO for OSAS in pediatric patients (≤18 years). Exclusively prospective studies with at least 10 patients were included and a last update was carried out in 2014.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that even today, the resulting trials are still cited in the contemporary scientific literature in national guidelines and publications [403]. Despite the extraordinary high frequency of the interventions [566], [567] plus the increasingly performed TOTO [107], [568] only few trials analyzed the clinical value of the interventions. This deserves a comment: …”
Section: Discussionmentioning
confidence: 99%